Splenic Mass and Isolated Gastric Varices: A Rare Presentation of a Neuroendocrine Tumor of the Pancreas - Shah, Sneha A; Amarapurkar, Anjali D; Prabhu, Sudesh R; Kumar, Vineet; Gangurde, Gautam K; Joshi, Rajeev M (JOP. Journal of the Pancreas, 2010)
Context Splenic involvement in neuroendocrine pancreatic tumors is well known but rarely presents as a primary splenic mass. Case report A rare case of a neuroendocrine tumor involving the tail of the pancreas, splenic hilum and splenic flexure of the colon, forming a conglomerate mass and presenting as isolated gastric varices is described. A 75-year-old male presented with hematemesis and melena. Esophagogastroduodenoscopy revealed isolated gastric varices. A CT scan revealed a mass predominantly involving the spleen and a small part of the pancreas. Conclusion A splenic mass with isolated gastric varices should be kept in mind as one of the presentations of a pancreatic neuroendocrine tumor. Image: Microscopy section from the spleen showing the neuroendocrine tumor.